2014
DOI: 10.1002/2014ja019893
|View full text |Cite
|
Sign up to set email alerts
|

Underlying scaling relationships between solar activity and geomagnetic activity revealed by multifractal analyses

Abstract: This paper identifies some scaling relationships between solar activity and geomagnetic activity. We examine the scaling properties of hourly data for two geomagnetic indices (a p and AE), two solar indices (solar X-rays X l and solar flux F10.7), and two inner heliospheric indices (ion density Ni and flow speed Vs) over the period 1995-2001 by the universal multifractal approach and the traditional multifractal analysis. We found that the universal multifractal model (UMM) provides a good fit to the empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For systematically characterizing the spatial heterogeneity of a fractal object, multifractal analysis (MFA) has been introduced 18 19 . MFA has been widely applied in many fields, such as financial modeling 20 21 , biological systems 22 23 24 25 26 27 28 29 30 31 32 , geophysical systems 33 34 35 36 37 38 39 40 and also complex networks 41 42 43 44 45 . Lee et al 46 mentioned that MFA is the best tool to describe the probability distribution of the clustering coefficient of a complex network.…”
mentioning
confidence: 99%
“…For systematically characterizing the spatial heterogeneity of a fractal object, multifractal analysis (MFA) has been introduced 18 19 . MFA has been widely applied in many fields, such as financial modeling 20 21 , biological systems 22 23 24 25 26 27 28 29 30 31 32 , geophysical systems 33 34 35 36 37 38 39 40 and also complex networks 41 42 43 44 45 . Lee et al 46 mentioned that MFA is the best tool to describe the probability distribution of the clustering coefficient of a complex network.…”
mentioning
confidence: 99%
“…As we all know, the binomial measures [41,42] produced by the p model have multifractal properties and its sacale index τ (q)function is known. We combine them with Gaussian noise to test the performance of MF-TWDPCCA.…”
Section: Multifractal Binomial Measuresmentioning
confidence: 99%
“…As is well known, multifractal analysis, which is a generalization of fractal analysis, has proved to be more powerful than fractal analysis in describing the spatial heterogeneity of complex objects. The tool of multifractal analysis has been widely used in many fields, including biological systems [30][31][32][33] and geophysical data analyses [34][35][36][37]. Many recent studies have shown that multifractal analysis performs well in characterizing the complexity of complex networks [24][25][26][27][38][39][40][41][42][43][44][45][46].…”
Section: J Stat Mech (2019) 073405mentioning
confidence: 99%